Analisis Penerapan Experiential Marketing Terhadap Minat Berkunjung Ulang Pada Objek Wisata Bayt Al-Qur’an Al-Akbar - Triansa Kurniawan; Esya Alhadi; Rini Rini (Politeknik Negeri Sriwijaya, 2022)
This study aims to determine the influence of the Experiential Marketing on Revisit Intention. This study uses descriptive quantitative research methods with data collection techniques through interviews, questionnaires, and documentation, this study uses purposive sampling technique with a sample of 100 respondents. The research data uses Multiple Linear Regression Analysis processed with IBM SPSS Ver 25. The results show that the Experiential Marketing have a positive relationship and have a significant effect on Revisit Intention.